From modernization to modes of production : - Taylor, John G. (Macmillan Press, 1979)
The aim of this book is to remedy this situation by directing its critique at the basic concepts operative in these theories, assessing the extent to which thay can adequately analyse the structure, reproduction and development of third-world societies.